Non-linear spring model for backfill grout-consolidation behind shield tunnel lining. (August 2021) - Liu, Xiao-Xue; Shen, Shui-Long; Xu, Ye-Shuang; Zhou, Annan
Abstract: This study presents a non-linear spring model for modelling the backfill grout consolidation behind shield tunnel lining. Two important parameters, i.e. the time-dependent grout pressure decay induced by consolidation and the grout-cake thickness, were derived through a non-linear spring model and continuity equation. The proposed non-linear spring model for backfill grout consolidation was validated based on vertical pressure and strain relationships determined from an oedometer test. The derived equations were applied to the Groene Hart Tunnel (GHT) project. The results show that the calculated grout pressures agree well with the measured values. The calculated grout-cake thicknesses are in good agreement with the measured values. Two key factors influencing the grout consolidation are discussed: grout diffusion into the soil, and the initial distribution of the grout injection pressure. It is found that grout diffusion into the soil can dissipate the grout pressure quicker than grout consolidation. The distribution of the initial grout injection pressure dominates the final distributions of the grout pressure/grout cake around the tunnel lining.